The Effect of Understanding of Accounting Standards and Internal Control Systems on the Quality of Financial Statements with the Application of Accounting Software as a Moderating Variable - Desmia Rahmadani; Dwiyanjana Santyo Nugroho (Eastasouth Institute, 2023)
This research examines the effect of understanding accounting standards and internal control systems on the quality of financial reports by applying accounting software as a moderating variable. The population of this research is MSMEs in DKI Jakarta. This study used a sampling technique, namely Proportional Stratified Random Sampling. The number of samples studied was 96 MSMEs in DKI Jakarta using a Likert scale measurement questionnaire. Testing the research data is done by testing the validity, reliability, classic assumption, and hypothesis tests. The results of this study indicate that the application of accounting software can strengthen the effect of understanding accounting standards and internal control systems on the quality of financial reports.